A new approach to frequency-domain noise analysis and design of a very-low noise amplifier in radio and microwave frequencies. (October 2017) - Sahoolizadeh, Hossein; Jannesari, Abumoslem; Dousti, Massoud
Abstract: This work presents a new idea to design and optimization of noise with a very-low-noise amplifier (VLNA). Noise optimization is done using suitable filters. An appropriate filter can convert circuit noise frequency response into a band stop. This is while the amplifier gain is in bandpass state. Hence, suitable gain and minimum noise are achieved in band pass. Using this approach in 0.13 µm CMOS technology, a VLNA in the frequency range of 20–1000 MHz is designed with the following specifications: minimum noise figure 0.95 dB, transfer gain 15.39 dB, third order intercept point −15.2 dBm at 900 MHz, die area of 0.075 mm 2, and power dissipation of 18.16 mW. To our knowledge, by comparison with recently reported LNAs, the presented LNA achieves the highest figure of merit (FOM) by taking into account the NF. Highlights: A new idea to design and optimization of noise is presented. The circuit noise frequency response is converted into a band stop. The method presented is based on adjusting gain poles and noise zeros.